Urban ethnography : legacies and challenges - Ocejo, Richard E. (Research in urban sociology, 2019)
Showcasing the ideas, analysis, and perspectives of experts in the method conducting research on a wide array of social phenomena in a variety of city contexts, this volume provides a look at the legacies of urban ethnography's methodological traditions and some of the challenges its practitioners face today.